Description Of The Caring Behavior Of Indonesian Nurses At Tokubetsu Original Yougoroujin Home Ayumien Tokyo 2022 - Mestiana Br Karo; Maria Martina Ernawati Wonga (Science Midwifery, 2022)
Caring behavior of nurses is our attitude and behavior to treat others we serve lovingly. Caring behavior is our attitude of concern for patients through empathy for patients and families. This study aims to find out an overview of the caring behavior of Indonesian nurses at Tokubetsu Yougoroujin Home Ayumien Tokyo Orphanage 2022. This study uses a total sampling technique, namely the number of respondents at the Tokubetsu Yougoroujin Home Ayumien Tokyo Orphanage are 48 respondents. The research instrument used a questionnaire of caring behaviors indonesian nurse tools. Based on demographic data, the results show that the male sex are 28 respondents (58.3%). Aged 75-90 years as many as 44 respondents (87.4%). Last High School Education are 33 respondents (68.8%). And the caring behavior of Indonesian nurses at the Tokubetsu Yougoroujin Home Ayumien Tokyo Home from 48 respondents was very good as many as 29 respondents (60.4%). Therefore, the caring behavior of nurses needs to be improved for the needs of patients